ANTIPROTOZOAL ACTIVITY OF THE CRUDE EXTRACT OF - GEORGE, SHIBUMON (International Journal of Pharmaceutical & Biological Archive, 2010)
New, effective antiprotozoal drugs are necessary to combat protozoal diseases. Based on this objective, a preliminary study was made by microscopic count method for assessing the antiprotozoal activity of the acetonic extract of Flacourtia inermis fruit against free-living protozoa and endo-commensal rectal ciliates of frog. Study shows that the fruit extract has excellent antiprotozoal activity against the tested organisms. Antiprotozoal study by microscopic count method can be considered as a preliminary test for detecting the antiprotozoal activity of the unknown sample.